PARETO SALES NETWORK ASSET AS CRITICAL SOURCES OF COMPETITIVE ADVANTAGE : A RESOURCE-BASED VIEW PERSPECTIVE - Yuswono, Irawan; Rahmadhani, Sari (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
Relationship skills can create a sales network and become an important part of a company to increase competitive advantage. The purpose of this study is to identify the inconsistency of the relationship between relational capability in competitive advantage and Pareto sales network assets as a mediator. The sample of this study came from food and beverage SME owners around the city of Semarang, Central Java. Respondent data was collected from 202 small and medium business sectors through questionnaires and interviews. This study used SEM-PLS for analysis. The results of the study found that (1) relational capability had a positive and significant effect on Pareto sales network assets; (2) relational capability has a positive and significant effect on competitive advantage; (3) Pareto sales network assets have a positive and significant effect on competitive advantage; (4) the greater the influence of relational capability on competitive advantage through Pareto sales network assets. The role of Pareto sales network assets has the potential to be a high leverage for competitive advantage in SMEs.